2004
DOI: 10.1897/03-173
|View full text |Cite
|
Sign up to set email alerts
|

Bioconcentration, biotransformation, and elimination of polycyclic aromatic hydrocarbons in sheepshead minnows (Cyprinodon variegatus) Exposed to Contaminated Seawater

Abstract: Sheepshead minnows (Cyprinodon variegatus) were continuously exposed to two concentrations of polycyclic aromatic hydrocarbons (PAHs) dissolved in seawater (sigma PAH = 7.57 and 72.31 microg/L) for 36 d, followed by 8 d of depuration. The PAHs studied were naphthalene (NPH or C0-NPH), phenanthrene (PHE or C0-PHE), pyrene (PYR), 2-methylnaphthalene (C1-NPH), 1,3-dimethylnaphthalene (C2-NPH), 2-isopropylnaphthalene (C3-NPH), 9-methylphenanthrene (C1-PHE), and 9-ethylphenanthrene (C2-PHE). Uptake rate constants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(63 citation statements)
references
References 42 publications
6
51
1
5
Order By: Relevance
“…N PH) is not as efficient as metabolism of HMWAHs (e.g. BaP) in some species of fish and birds (Roubal et al 1977, Varanasi & Gmur 1981, Jonsson et al 2004, Troisi et al 2006. Data collected in the current study clearly demonstrated that externally oiled turtles had absorbed petroleum-related PAHs via ingestion as well as inhalation (based on gastrointestinal and lung PAH findings, respectively), and that they had metabolized these compounds in the liver to more polar fluorescent aromatic compounds that were measured in their bile.…”
Section: Tissue Differences In Pah Concentrations and Implications Fomentioning
confidence: 99%
“…N PH) is not as efficient as metabolism of HMWAHs (e.g. BaP) in some species of fish and birds (Roubal et al 1977, Varanasi & Gmur 1981, Jonsson et al 2004, Troisi et al 2006. Data collected in the current study clearly demonstrated that externally oiled turtles had absorbed petroleum-related PAHs via ingestion as well as inhalation (based on gastrointestinal and lung PAH findings, respectively), and that they had metabolized these compounds in the liver to more polar fluorescent aromatic compounds that were measured in their bile.…”
Section: Tissue Differences In Pah Concentrations and Implications Fomentioning
confidence: 99%
“…It is therefore necessary not only to identify these pollution sources but also to monitor and manage their effects on the health of aquatic ecosystem (Jiraungkoorskul et al, 2006). Bioconcentration of PAHs from water into fish tissue depends on the balance between uptake and elimination rates (Jonsson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…• A través del agua marina contaminada, que afecta a los organismos acuáticos incorporando los HAPs transportados por el agua o a partir de sedimentos contaminados (Jonsson et al, 2004). La acumulación de grandes cantidades de HAPs por los moluscos bivalvos permite su utilización como bioindicadores de contaminación medioambiental.…”
Section: Exposición De La Poblaciónunclassified